Comment on "Bi-layering at ionic liquid surfaces: a sum – frequency generation vibrational spectroscopy – and molecular dynamics simulation-based study" by T. Iwahashi, T. Ishiyama, Y. Sakai, A. Morita, D. Kim and Y. Ouchi, Phys. Chem. Chem. Phys., 2020, 22, 12565. Issue 8 (17th February 2021) - Deutsch, Moshe; Magnussen, Olaf M.; Haddad, Julia; Pontoni, Diego; Murphy, Bridget M.; Ocko, Benjamin M.
Abstract : Serious discrepancies are demonstrated between the proposed mono/bilayer surface structure and X-ray measurements, which rather support a depth-decaying multilayer surface structure. Abstract : This Comment raises several questions concerning the surface structure concluded in the paper referenced in the title. Specifically, that paper ignores previous experiments and simulations which demonstrate for the same ionic liquids depth-decaying, multilayered surface-normal density profiles rather than the claimed molecular mono- or bi-layers. We demonstrate that the claimed structure does not reproduce the measured X-ray reflectivity, which probes directly the surface-normal density profile. The measured reflectivities are found, however, to be well-reproduced by a multilayered density model. These results, and previous experimental and simulation results, cast severe doubt on the validity of the surface structure claimed in the paper referenced in the title.